2018
DOI: 10.5582/bst.2018.01264
|View full text |Cite
|
Sign up to set email alerts
|

On medical application of neural networks trained with various types of data

Abstract: Neural networks have garnered attention over the past few years. A neural network is a typical model of machine learning that is used to identify visual patterns. Neural networks are used to solve a wide variety of problems, including image recognition problems and time series prediction problems. In addition, neural networks have been applied to medicine over the past few years. This paper classifies the ways in which neural networks have been applied to medicine based on the type of data used to train those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Current artificial intelligence models can achieve diagnostic performance comparable to those of medical experts in various domains 16 18 . In the present study, we demonstrated that voice features such as mel-spectrogram can be represented as an image and used as inputs for CNN.…”
Section: Discussionmentioning
confidence: 99%
“…Current artificial intelligence models can achieve diagnostic performance comparable to those of medical experts in various domains 16 18 . In the present study, we demonstrated that voice features such as mel-spectrogram can be represented as an image and used as inputs for CNN.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial neural network modeling is a powerful tool that can harness the value of large and complex datasets and that, in the era of “big data,” is of increasing interest in medical diagnostics (imaging and histopathology in particular) and prognostics 28,29 . Disease predictions from ANN models are not limited by an understanding of the associated pathophysiology because they are based purely on mathematical relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews of deep learning for medical images highlight the vast amount of emerging research in this field [44,70,112]. On the chest X-rays dataset, various CNN based methods have been suggested.…”
Section: Image Annotationmentioning
confidence: 99%